Non-Transferable Months of Parental Leave: Trends in Fathers’ Behavior - Galdauskaitė, Dovilė; Maslauskaitė, Aušra (Socialinė teorija, empirija, politika ir praktika, 2026)
An equal sharing of childcare responsibilities between men and women is a family policy priority in the European Union (EU), as emphasized in many EU strategic documents. Among the latest is EU Directive 2019/1158 on work-life balance for parents and carers (EU, 2019), which requires countries to introduce measures that encourage fathers to take on childcare responsibilities to balance family and professional life. At the national level, the directive has been implemented in various ways; in some countries, a new type of leave targeting fathers has been introduced. This paper focuses on Lithuania, where parental leave policies were modified in 2023, and a new type of leave was thus introduced: Non-Transferable Parental Leave Months (NTPM). The NTPM leave is designed as a “take it or leave it” policy scheme. This paper aims to identify trends in the uptake of NTPM by fathers in Lithuania, and to reveal socio-economic and family-related factors that contribute to the use of this new family policy measure. The theoretical foundations of the study are Walby’s (2024) concept of the gender regime, which explains gender relations and structures at the macro level, and the resource bargaining perspective, which examines interactions at the micro level of the family. Our analysis is based on a dataset which links national registers and Lithuanian Social Insurance Agency data. Consequently, our analysis includes about 84 thousand individuals entitled to NTPM and other forms of parental leave in 2023–2024, covering a period of 24 months. Descriptive analysis reveals that only 16 percent of fathers used the NTPM, making it the less popular option than the paternity leave and slightly more popular than parental leave. By contrast, 54 percent of fathers took the ‘daddy month’ and 12 percent took parental leave. There are significant socio-economic differentials at the individual and couple levels in the use of the NTPM by fathers. Our results show that the NTPM is used more frequently by couples with lower levels of income, thus suggesting that they adopt an economic utility strategy.